Beyond conventional biomarkers: Emerging importance of extracellular vesicles in osteoarthritis, metabolic disorders and cardiovascular disease - Madison Coward-Smith; Ye Zhang; Chantal Donovan; Richard Y. Kim; Baoming Wang; Razia Zakarya; Hui Chen; Jiao Jiao Li; Brian G. Oliver (Extracellular Vesicle)
Extracellular vesicles (EVs), initially recognized for their roles in intercellular communication, are being increasingly explored for applications in the diagnosis and therapy of various diseases, particularly those driven by chronic inflammation. This review provides insight into the defining characteristics and functions of EVs, focusing on their role in contributing to and acting as potential therapeutics for chronic inflammatory diseases, including osteoarthritis, metabolic disorders such as obesity and metabolic dysfunction associated fatty liver disease, and cardiovascular diseases such as atherosclerosis and ischaemic stroke. Finally, the issues limiting EV translation from bench to bedside, and the outlook of EV research are discussed.